The sports results of leading pentathlonists during 2000-2010. - Pityn M.P; Stetskovich S.R (Kharkov National Pedagogical University, 2011)
The result sports changes of leading sportsmen of the world in modern pentathlon are considered in the paper. During the investigation process the competition rules changes were determined and what have affected on the sports result in the modern pentathlon. The winner results changes and top ten sportsmen of the world championships and the Olympic Games were characterized during 2000-2010. The rules changes influence of the competition holding on the results of competitive activity of high qualification pentathlonists were established.